Isolation of Endothelial cells from Goat Umbilical artery by an Optimized Technique and Characterisation by Cellular Morphology and Immunocytochemistry - Mohanty, Ipsita; Suklabaidya, Sujit; Malik, Hrudananda; Das, Biswajit; Parija, Subas Chandra (Current trends in biotechnology and pharmacy, 2017)
The aim of the present study is to isolate endothelial cells from goat umbilical artery and to characterise them according to gross morphological and immunological criteria. A relatively simple, effective and less time consuming method was used for the first time to isolate and characterise goat umbilical artery endothelial cells (GUAEC). The isolated GUAECs were identified by cellular morphology and immunocytochemistry. Endothelial cells isolated were homogeneous in nature, oval shaped, with distinct cell borders and centrally located nucleus. It followed a striated array growth pattern. The growth curve of goat endothelial cells exhibited a typical ‘S’ shape. Von Willebrand factor VII and Ulexeuropaeus agglutinin-I were confirmed by immunocytochemistry. VEGF transcripts were positive from these endothelial cells by RT-PCR. In conclusion, the findings of the present study for GUAEC isolation may allow more detailed analysis of their biological properties and pharmacological characteristics thus promoting successful application of translational research in vascular biology.